The impact of employees' perceptions regarding hotels’ green intellectual capital on their environmental perceptions: A mediating moderation model - Ertac Gulakdeniz; Georgiana Karadas (Heliyon)
Researchers acknowledge the significance of hotels' environmental performance, however they call for a further comprehensive examination of the aspects that serve as its drives. Moreover, despite the abundance of studies on environmental performance in the hospitality literature, employees' perceptions regarding hotels' green intellectual capital and its potential outcomes are scarcely investigated. With this realization, and building upon the job demand-resource theoretical framework and socially embedded theoretical framework of thriving, the current paper proposes a conceptual model where thriving at work mediated the impact of employees' perceptions regarding hotels' green intellectual capital on environmental performance moderated by work-related enterprise social media usage. To gauge these relationships, data was collected from frontline employees working in four and five star Turkish hotels. The study's interrelationships have been analyzed by employing structural equation modeling. The study revealed that employees' perceptions of hotels' green intellectual capital significantly influenced their thriving at work and positively shaped their views on hotels' environmental performance. Additionally, thriving at work demonstrated a significant impact on employees' perceptions of hotels' environmental performance, acting as a mediator between perceptions of green intellectual capital and environmental performance. Furthermore, the study found that the influence of employees' perceptions of hotels' green intellectual capital on thriving at work was moderated by work-related enterprise social media usage. According to our findings, top management should monitor and promote employees' perceptions of green intellectual capital, and their thriving at work, sustaining a green organizational culture at the same time via an effective usage of enterprise social media to foster environmentally friendly initiatives. This could involve creating platforms for idea-sharing and recognizing employees who implement sustainable practices.